Microsoft Windows XP - June Jamrich Parsons (Thomson Course Technology, 2006)
New Perspectives on Windows XP-Comprehensive, 2005 Service Pack 2 Update offers new coverage on how to protect your computer using the new Security Center features that are part of Windows Service Pack 2, including the Windows Firewall, Automatic Updates, and Virus Protection. This critical information ensures that students are prepared to protect their PCs from security and privacy threats